Versatile Preparation of Nonspherical Multiple Hydrogel Core PAM/PEG Emulsions and Hierarchical Hydrogel Microarchitectures1. (4th June 2014) - Guo, Song; Yao, Tong; Ji, Xiaobo; Zeng, Changfeng; Wang, Chongqing; Zhang, Lixiong
Abstract The preparation of nonspherical materials composed of separated multicomponents by droplet‐based microfluidics remains a challenge. Based on polymerization‐induced phase separation and droplet coalescence in microfluidics, we prepared emulsions of variously shaped PAM/PEG core/shell droplets and hydrogels composed of two separated components, which show flexible and transformable hierarchical structures and microarchitectures. We find that AM/PEG aqueous droplets form a core/shell structure after polymerization resulting from phase separation. Thus multicore/shell droplets are easily produced by coalescence of core/shell structures. By changing the polymerization temperature and the flow rate, the morphology of the multicore droplets and the hydrogel can be easily adjusted. The hydrogels exhibit apparent anisotropy and different protein release rates depending on their structures. The preparation technique is simple and versatile and the resulting hydrogels have potential applications in many fields.